A student-staff partnership conducting research in higher education: An analysis of student and staff reflections - Payne, Helen; Cantwell, James; Bristow, Richard (International Journal for Students as Partners, 2023)
This article reports on an analysis of reflections by students and staff following a student-staff partnership which conducted a qualitative exploratory inquiry case study on student mental health in higher education. Following completion of the inquiry, two engaged students and the principal investigator reflected on their experience of the partnership. The analysis resulted in the following categories: a) benefits, b) support for learning, c) motivations, d) impact, e) outputs, and f) limitations. Students learned research skills, enhancements for learning/career and empowerment. Staff experienced an eased ability to conduct research and the rewards of seeing students develop new skills. It is recommended stakeholders in higher education continue to invest in student-staff partnerships in the context of research studies and mental health inquiry to foster opportunities for positive learning outcomes for students, staff, and institutions.